2023
DOI: 10.1001/jamanetworkopen.2023.8422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treadmill Perturbation-Based Balance Training on Fall Rates in Community-Dwelling Older Adults

Abstract: ImportanceFalls are common and the leading cause of injuries among older adults, but falls may be attenuated by the promising and time-efficient intervention called perturbation-based balance training (PBT).ObjectiveTo evaluate the effects of a 4-session treadmill PBT intervention compared with regular treadmill walking on daily-life fall rates among community-dwelling older adults.Design, Setting, and ParticipantsThis 12-month, assessor-blinded randomized clinical trial was conducted from March 2021 through D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
(175 reference statements)
0
2
0
1
Order By: Relevance
“…Exercise, especially multi-component exercise, can prevent, delay and reverse frailty, and improve the physical fitness of pre-frail/frail older adults [ 56 , 57 ]. Regular physical activity improved physical function and balanced performance, reducing the risk of falls among older individuals [ 58 , 59 ]. Proper strength training can help combat sarcopenia by preventing muscle loss and increasing both muscle mass and strength [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise, especially multi-component exercise, can prevent, delay and reverse frailty, and improve the physical fitness of pre-frail/frail older adults [ 56 , 57 ]. Regular physical activity improved physical function and balanced performance, reducing the risk of falls among older individuals [ 58 , 59 ]. Proper strength training can help combat sarcopenia by preventing muscle loss and increasing both muscle mass and strength [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 PBT may also hold great promise as a highly efficient fall prevention strategy in older adults, though current evidence is still not sufficient. While some studies found no fall-reducing effect of low-volume PBT, 26 27 other studies showed an impressive reduction in (trip-related) falls of about 50% over a 12-month follow-up period after just one and four PBT sessions, respectively. 28 29 This corresponds roughly to twice the effect of well-established fall prevention programmes, 14 while the training volume is significantly lower.…”
Section: Introductionmentioning
confidence: 94%
“…Nach dieser einmaligen Intervention reduzierten sich die Sturzereignisse im Folgejahr relativ zur Kontrollgruppe um über 40 Prozent. Dementgegen konnte eine kürzlich publizierte Studie in Dänemark bei gesunden älteren Menschen lediglich eine nicht signifikante 22 % Reduktion nach 80 Min multidirektionalem PBT, verteilt über vier TE, erzielen[130]. Auch ein erster pragmatischer RCT wurde inzwischen publiziert[131].…”
unclassified